Pengaruh Lingkungan Kerja, Pelatihan, Motivasi Dan Komitmen Organisasi Terhadap Kinerja Pegawai Tata Usaha Sekretariat Daerah Kabupaten Malang - Yuli Khoiriyah; Rois Arifin; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract This study aims to determine and analyze the influence of the Work Environment, Training, Motivation, and Organizational Commitment to the Performance of the Secretariat Administrative Staff of Kabupaten Malang.The population used in this study were 46 employees of the Secretariat Administrative Staff of Kabupaten Malang by utilizing the saturated sample method (census sample). The method used in this study was quantitative research method in which the data analysis technique used is multiple linear regression by using SPSS ver.16.This study proves that the variables of Work Environment, Training, Work Motivation, and Organizational Commitment simultaneously and partially have a significant effect on employee performance in the Secretariat Administrative Staff of Kabupaten. Adjusted R2 of 0.598 explains that 59.8% of employee performance in Secretariat Administrative Staff of Kabupaten Malang can be explained by the variables of Work Environment, Training, Work Motivation, and Organizational Commitment and 40.2% is caused by other variables which are not observed. Keywords: Work Environment, Training, Motivation, Organizational Commitment, Employee Performance.